Fighting fair: community perspectives on the fairness of performance enhancement in esports - Friehs, Maximilian A.; Klarkowski, Madison; Frommel, Julian; Phillips, Cody; Mandryk, Regan L. (Frontiers in Sports and Active Living, 2024)
Aims: This study aims to explore community perspectives on enhancer usage in competitive gaming and esports, focusing on the perception of fairness and concerns about various potential performance enhancers. Methods: We conducted both qualitative and quantitative surveys to understand the competitive gaming community's opinions on different types of performance enhancers and their potential impact on esports. A thematic analysis was performed to identify key themes in how players rationalize their opinions. Conclusions: The gaming community differentiates between potential performance enhancers based on how problematic they are for the esports scene, with the most concern surrounding hard drugs, pharmaceuticals, and brain stimulation interventions. Participants who are more invested in competitive gaming tend to be more sceptical of enhancers and express greater concerns. Four themes were identified in the thematic analysis: (1) risk, (2) morality, (3) enhancer effects, and (4) regulation. To increase acceptance and perceived legitimacy in decision-making, it is recommended that regulators engage a variety of stakeholders in transparent decision-making processes when forming tournament rules and regulations. This will help address the fragmented regulatory landscape and prevent potential differences in the perception of tournament winners based on the governing body supervising the competition.